Diagnostic perspectives in the reumathological vasculitis: the role of the videocapillaroscopic analysis - C. Pizzorni; A. Sulli; C. Craviotto; M. Tuccio; B. Seriolo; M. Cutolo (PAGEPress Publications, 2002)
Microvascular involvements represent one of the first step in many autoimmune diseases such as scleroderma (SSc) or antiphospholipid syndrome. Early in the disease, the peripheral microangiopathy may be well recognised and studied by nailfold videocapillaroscopy (NVC), a noninvasive and safe technique, that is reported to have both diagnostic and prognostic value, especially in the presence of Raynaud's phenomenon (RP). The classification of defined major NVC patterns in SSc might be useful in assessing the appearance and progression of the sclerodermic microangiopathy. In addition, the NVC changes might represent a morphological reproduction of the evolution of the SSc. The early appearance of giant capillaries and haemorrhages (Early pattern) is of great relevance for the early diagnosis of the SSc. Therefore, these alterations are more evident in the active phase of the disease (Active pattern). Converserly, the NVC observation of loss of capillaries, vascular architectural disorganisation and the presence of ramified/ bushy capillaries (Late pattern) represents the clearest aspect of advanced SSc microvascular damages. Interesting, correlations between the NVC and clinical aspects of SSc, as well as the effects of therapeutical intervenctions have been observed.